2019
DOI: 10.1037/pspp0000241
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic score for educational attainment captures DNA variants shared between personality traits and educational achievement.

Abstract: Genome-wide polygenic scores (GPS) can be used to predict individual genetic risk and resilience. For example, a GPS for years of education (EduYears) explains substantial variance in cognitive traits such as general cognitive ability and educational achievement. Personality traits are also known to contribute to individual differences in educational achievement. However, the association between EduYears GPS and personality traits remains largely unexplored. Here, we test the relation between GPS for EduYears,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 102 publications
3
41
1
Order By: Relevance
“…In this respect, the scientific literature shows studies that relate personality, through the five-factor model, with academic performance. Thus, agreeableness, and intellect/imagination (also known as openness) are related to academic performance (Poropat, 2009;Smith-Woolley et al, 2019). Specifically, conscientiousness predicts academic achievement (O Connor and Paunonen, 2007), which is expected to be found in the present study.…”
Section: Personalitysupporting
confidence: 60%
See 1 more Smart Citation
“…In this respect, the scientific literature shows studies that relate personality, through the five-factor model, with academic performance. Thus, agreeableness, and intellect/imagination (also known as openness) are related to academic performance (Poropat, 2009;Smith-Woolley et al, 2019). Specifically, conscientiousness predicts academic achievement (O Connor and Paunonen, 2007), which is expected to be found in the present study.…”
Section: Personalitysupporting
confidence: 60%
“…A review of the scientific literature has shown that many studies have analyzed the relationship between academic achievement and different psychological constructs such as self-concept (Susperreguy et al, 2018;Wolff et al, 2018;Sewasew and Schroeders, 2019), personality (Janošević and Petrović, 2019;Perret et al, 2019;Smith-Woolley et al, 2019), and emotional intelligence (Corcoran et al, 2018;Deighton et al, 2019;Piqueras et al, 2019). In this work, these psychological constructs are analyzed together with primary school children by gender and cultural group.…”
Section: Introductionmentioning
confidence: 99%
“…The final GPS is obtained as the sum of the trait-increasing alleles (each variant coded as 0, 1, or 2), weighted by the posterior effect size estimates. In contrast to clumping and thresholding, LDpred retains all the SNPs in the polygenic score that are common between GWA summary statistics and genotype data in the target sample (for more details about this polygenic score calculation approach, see 15 ). In this study, we created polygenic scores using a prior that assumes a causal fraction of 1 for all analyses, based on the assumption that all genetic markers contribute to trait development.…”
Section: Methodsmentioning
confidence: 99%
“…SES) also contribute to the development of other behavioural traits through prGE mechanisms. Although it has been suggested that the widespread cross-trait associations between the EA GPS and various outcomes may be partly driven by prGE effects 15,22 , to our knowledge no study to date has tested this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation